Quantitative assessment of placental perfusion by contrast-enhanced ultrasound in macaques and human subjects - Roberts, Victoria HJ (Am J Obstet Gynecol, 2016)
BACKGROUND: The utero-placental vascular supply is a critical determinant of placental function and fetal growth. Current methods for the in vivo assessment of placental blood flow are limited. OBJECTIVE: Here we demonstrate the feasibility of utilizing contrast-enhanced ultrasound to visualize and quantify perfusion kinetics in the intervillous space of the primate placenta. STUDY DESIGN: Pregnant Japanese macaques were studied at mid second trimester and in the early third trimester. Markers of injury were assessed in placenta samples from animals with or without contrast-enhanced ultrasound exposure (n=6/group). Human subjects were recruited immediately prior to scheduled first trimester pregnancy termination. All studies were performed with maternal intravenous infusion of lipid-shelled octofluoropropane microbubbles with image acquisition using a multipulse contrast-specific algorithm with destruction-replenishment analysis of signal intensity for assessment of perfusion. RESULTS: In macaques, rate of perfusion in the intervillous space was increased with advancing gestation. No evidence of microvascular hemorrhage or acute inflammation was found in placental villous tissue and expression levels of caspase-3, nitrotyrosine and HSP70 as markers of apoptosis, nitrative and oxidative stress respectively were unchanged by contrast-enhanced ultrasound exposure. In humans, placental perfusion was visualized at 11wks gestation and preliminary data reveal regional differences in intervillous space perfusion within an individual placenta. By electron microscopy, we demonstrate no evidence of ultrastructure damage to the microvilli on the syncytiotrophoblast following first trimester ultrasound studies. CONCLUSIONS: Use of contrast-enhanced ultrasound did not result in placental structural damage, and was able to identify intervillous space perfusion rate differences within a placenta. Contrast-enhanced ultrasound may offer a safe clinical tool for the identification of pregnancies at-risk for vascular insufficiency; early recognition may facilitate intervention and improved pregnancy outcomes.